2015
DOI: 10.1080/01431161.2014.999386
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of environmental changes induced by internally displaced person (IDP) camps in the Darfur region, Sudan, based on multitemporal MODIS data

Abstract: Darfur's complex conflict situation led to large-scale internal displacement of people with significant implications for the environment as well as for the conflict situation itself. Time series analyses of medium-resolution satellite data for monitoring large regions were carried out over a longer period to detect the impact of camps for internally displaced persons (IDPs) on their surrounding environment. Four regions of interest were defined in the Darfur region, Sudan, which cover the main and most dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…For example, an evaluation of the changes in landscape within 90 km of Darfur camps in 2001-2007 illustrated a regeneration of vegetation in the rural residences of the displaced while an intensification of agricultural practices in the urban periphery [15]. Extending the temporal coverage to 2010 and refining the spatial resolution to 250 m indicates that the deleterious impacts on vegetation are quite concentrated in the areas surrounding the camps [18]. In utilizing data at a greater spatial resolution, our study may underestimate the scale of agricultural deforestation induced by refugees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, an evaluation of the changes in landscape within 90 km of Darfur camps in 2001-2007 illustrated a regeneration of vegetation in the rural residences of the displaced while an intensification of agricultural practices in the urban periphery [15]. Extending the temporal coverage to 2010 and refining the spatial resolution to 250 m indicates that the deleterious impacts on vegetation are quite concentrated in the areas surrounding the camps [18]. In utilizing data at a greater spatial resolution, our study may underestimate the scale of agricultural deforestation induced by refugees.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to testing the refugee effect on the condition of natural vegetation, we test a second hypothesis: refugee camps lead to the expansion of agricultural land [18][19][20]. Refugee camps offer additional sources of cheap labor and attract capital investment, such as the expansion of road networks [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence has shown that for these reasons such camps often have significant impacts on the environment (e.g. HAGENLOCHER et al 2012, KRANZ et al 2015. Severe deforestation, desertification, land degradation, unsustainable groundwater extraction, and water pollution are impacts that can be observed in the surroundings of many camps, often within a radius of up to 15 km.…”
Section: Introductionmentioning
confidence: 99%